Uso do ácido ursodesoxicólico no pós-operatório imediato para a prevenção de litíase biliar em pacientes submetidos à derivação gástrica em Y de ROUX - Machado, Francisco Heine Ferreira (2016)
The aim of the present study was to evaluate prospectively the influence of ursodeoxycholic acid (UDCA) administration in the prevention were cholelithiasis in the first six months after Roux-en-Y gastric bypass surgery. The data was collected through questionnaires which investigate demographic and anthropometric characteristics. Medical records were analysed to evaluate comorbidities as hepatic steatosis, gastroesophageal reflux disease, gastritis, Hypertension, cardiovascular disease, dyslipidemia, osteoarthritis and infertility. Therefore, 137 patients, with whom 69 were from Monsenhor Bruno Clinic (GROUP A) and 68 were from the Obesity Nucleus of Ceará (GROUP B), were sellected. The patients from GROUP A group received UDCA, while the patients from GROUP B, group did not received UDCA. The quantitative categorical results were presented as percentages and counts, and the numerical results were measured as central trend measures. Normality tests were performed for the numerical variables. According on the variables normality, ANOVA or Mann-Whitney tests were performed. For categorical variables, the chi-square test was performed. For paired variables, the McNemar test was applied. The odds ratio were calculated to measure the strength of association between UCDA exposure and the disease. P values up to 0.05 were considered significant. The data were analyzed using Statistical Package for the Social Sciences (SPSS), v23, SPSS, Inc.. There was no statistical significance in the formation or not of the cholelithiasis (p = 0.110) between GROUP A or GROUP B patients according to the naturality.The gender (p = 0.090) and marital status (p = 0.663) did not presented statistical significance either. In the GROUP A group, 68 (57,6%) did not developed cholelithiasis and 1 (5,3%) developed cholelithiasis. In the GROUP B group, 50 (42,4%) did not developed cholelithiasis, while 18 (94,5%) developed this disorder (OR= 24,4, IC95%= 3,1-189,4, p< 0,001). In the GROUP A group, 64 (92,6%) patients did not presented hepatic steatosis and 5 (7,4%) persisted with hepatic steatosis. In the GROUP B group, hepatic steatosis was not evidenced in 68 (100%) patients, however, it was significant to form cholelithiasis (p< 0,024). The others cormobities evalueted presented significative improvement. The results demonstrate that patients from NOC group, who had not received UDCA, had a higher chance of developing cholelithiasis when comparing with the patients from GROUP A group, who had received UDCA (OR= 24,4, IC95%= 3,1-189,4, p< 0,001).